Fuzzy trust model for wireless sensor networks with intrusion tolerance - WANG Liang-min1; GUO Yuan-bo2; ZHAN Yong-zhao1 (Tongxin xuebao)
To protect key services of wireless sensor networks of data fusion and package forward,a fuzzy trust model based on trust and confidence and its evaluation algorithms were presented,in which the value of confidence was used to describe the impreciseness of the value of the trust.Then the simulation and the example were given to show the per-formances of using the model to detect or tolerate the insidious attacks.Finally,the package drop ration of the networks with the trust evaluation system was simulated and the comparison with the related work was discussed.